The church's ministry to Filipino women domestic helpers in Hong Kong - Anga-angan, Arlene U. (Quezon City : St, Andrew's Theological Seminary, 1993)
"The field exposure of this writer in the summer of 1992 in Hongkong is an experience she will treasure in her lifetime. Since that summer of 1992, the writer has had sleepless nights whenever this experience is remembered. There she saw the fast life of modern city. But it was also there where she had encountered a very unusual experience accorded to our own Filipino women. The families that were left behind or were left in the Philippines may not know of such experience, but the Filipino domestic helpers in Hongkong consider it their fate because the want to earn some dollars. Thus it seems glamorous and even a dream for many Filipinos to be able to work abroad to earn the " Almighty American dollars". This was also noted by the Natinal Council of Churches in the Philippines in its report that " from 1986 to 1989, the Philippine Overseas Employment Administration (POEA) processed to a total of 1, 912, 065 workers for deployment overseas." Perhaps the number today could have increased further due to the economic losses the Philippine economy has been incurring due to the 8-12 hours of brownouts everyday. Before we get drowned with the statistics, we should ask ourselves what the government, the non-governmental agencies and the church are doing for the millions of overseas contract workers? Are we just contented to know that "overseas workers remitted through the official banking channels $3.38 billion from 1986 to 1989 and thus the number one dollar earner for the country." Based on the above considerations, the writer would like to study more closely the predicament of the Filipino women working as domestic helpers in Hongkong."--Introduction
A mini thesis submitted to the faculty
in partial fulfillment of the requirements of Master in Divinity
Thesis (M.Div.)- St. Andrew's Theological Seminary, Quezon City